INTERNALISASI BAHASA ASING SEBAGAI UPAYA MEMBANGUN SUMBER DAYA MANUSIA GENERASI MILENIAL - Uswatun Hasanah; Yusfar Ramadhan; Izzat Amini (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2022)
The implementation of foreign language learning in Indonesia is an effort for the Indonesian people to be able to absorb and follow the development of science and technology in the world, as well as a way to enter the global society. The people of Banjar Talela Village want introductions to linguistic skills (Arabic and English) for children and the younger generation as an effort to develop human resources so that they can motivate them to move forward and compete in the global world. This form of language learning has been carried out in this village as a form of service to the local community, by carrying out various extra-curricular activities and intra- curricular activities. The internalization of foreign languages is carried out in various ways, including; 1) Be a role model for children and youth in speaking of foreign languages (Arabic and English) in their daily life. 2) Teach vocabularies (English or Arabic) everyday. 3) Teach various linguistic activities according to their talents and interests such as poetry, stories, sermons etc. 4) Simulate how they can use vocabularies (English or Arabic) in their daily life.Â